PEMBERDAYAAN EKONOMI MASYARAKAT DESA CAPA PALOH MELALUI SISTEM PERTANIAN TERINTEGRASI BERBASIS PROGRAM INOVASI DESA DAN POTENSI LOKAL - Julia; Hamdani; Ibnu Yasier; Fahmi, Nuzulul; Abubakar, Al Asri; Junaidi; Karnilawati; Safrika; Malia, Rezqi (Yayasan Sagita Akademia Maju, 2023)
Economic empowerment is an important tool in improving the community's economy. The Integrated System is basically an integrated agricultural system that is capable of being an important choice of strategy to increase resilience, security, food quality and improve the community's economy. One of the solutions in developing integrated agriculture is to utilize the Village Innovation and Local Potential Program. This community service program aims to increase people's knowledge of integrated agriculture by taking advantage of village innovation program offers in terms of supporting local potential to improve the economy. The method used in this activity is counseling on integrated agriculture in building food security by taking advantage of village innovation program offers and local potential. The partners for this activity are all the people of Gampong Capa Paloh, Padang Tiji District, Pidie Regency. From this activity it can be concluded that the partner community is very active during the implementation of activities in the context of empowering the community's economy in Gampong Capa Paloh